PENGARUH PENAMBAHAN EKSTRAK DAUN ALPUKAT (Persea americana, mill) TERHADAP MUTU ORGANOLEPTIK DAN KADAR KALIUM PUDING PISANG - Putri Aulia Arza; Suci Purnama Sari (JURNAL PENDIDIKAN DAN KELUARGA, 2018)
Leaf avocado (Persea americana, mill) and Banana Mas (Moses sp) is a plant that has high potassium content and low levels of sodium. The purpose of this research is to analyze the effect of addition of avocado leaf extract to organoleptic quality and potassium banana pudding level. Type of research is true experimental with completely randomized design method. The data used was obtained directly from 25 semi trained panelists. Data analyzed by using ANOVA, if different real continued with Test Duncan. Addition of Leaf avocado and Banana Mas affect the levels of acceptance in terms of color, aroma and flavor but does not affect the texture. Addition of eggs also affects the level of potassium. Best assessment results obtained on treated banana with the addition of avocado leaf extract as much 250 ml ©. Potassium content of pudding with adding leaf avocado 0, 200ml dan 250ml respectively 0,0365 %, 0,0577 %, 0,0790 %